Implementasi Sistem Informasi Manajemen dalam Mendukung Proses Pembelajaran Daring pada Pendidikan Anak Usia Dini - Rani Astria Silvera Harahap; Rahyana Hasibuan (Universitas Islam Tribakti Lirboyo Kediri, 2022)
In order to achieve the expected educational goals, teaching and learning activities at school institutions will be better if a school institution has an information system that can manage the learning activities carried out. A management information system is a system that can make it easier for a leader to obtain information in making decisions. This research is a library research with descriptive qualitative methods. Seeing the importance of the role of the management information system for an institution, school institutions should provide information systems with various forms according to the level of school needs. The development of information technology runs so quickly, especially in ECCE institutions, such as during the pandemic, learning is still carried out even though they are not face to face. Learning is carried out remotely (online) through social networks and special platforms that are connected via the internet whose implementation is of course assisted by parents. In addition, it is easier for students to obtain learning materials by utilizing existing information technology so that the learning carried out takes place effectively and efficiently.